The Living Transcendental — An Integrationist View of Naturalized Phenomenology - Netland, Thomas (Frontiers in Psychology, 2020)
In this article I take on the "Transcendentalist Challenge" to naturalized phenomenology, highlighting how the ontological and methodological commitments of Merleau-Ponty’s philosophy point in the direction of an integration of the transcendental and the empirical, thus making room for a productive exchange between philosophy and science when it comes to understanding consciousness and its place in nature. Discussing various conceptions of naturalized phenomenology, I argue that what I call an "Integrationist View" is required if we are to make sense of the possibility of productive exchange between phenomenology and the sciences. My main argument is that if we conceive of consciousness as a structure of behavior ontologically prior to the distinctions between objectivity and subjectivity and third- and first-person perspectives, we arrive at a view of the transcendental as not essentially separate from the empirical, but rather as contingent organizational norms of empirical nature that are best illuminated through a dialectical exchange between phenomenological and scientific approaches. I end by showing how Merleau-Ponty's engagement with the "Schneider case" in an example of such an integration.